2021
DOI: 10.3389/fcell.2020.622215
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Membrane Contact Sites in Cancer Progression

Abstract: Membrane contact sites (MCS) are typically defined as areas of proximity between heterologous or homologous membranes characterized by specific proteins. The study of MCS is considered as an emergent field that shows how crucial organelle interactions are in cell physiology. MCS regulate a myriad of physiological processes such as apoptosis, calcium, and lipid signaling, just to name a few. The membranal interactions between the endoplasmic reticulum (ER)–mitochondria, the ER–plasma membrane, and the vesicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 225 publications
(255 reference statements)
2
15
0
Order By: Relevance
“…Converging evidences in the literature indicate that, after synthesis in the ER, the transport of chol is fast and carried between membranes by lipid transfer proteins. We here showed that the ER-PM contact sites were more extended in the malignant cells, in agreement with their proposed role in cancer progression [ 47 , 48 ]. Moreover, chol depletion decreased both ER-PM contacts and chol surface exposure, consistent with the accumulation of ER-resident proteins at ER-PM contact sites upon chol supplementation [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 88%
“…Converging evidences in the literature indicate that, after synthesis in the ER, the transport of chol is fast and carried between membranes by lipid transfer proteins. We here showed that the ER-PM contact sites were more extended in the malignant cells, in agreement with their proposed role in cancer progression [ 47 , 48 ]. Moreover, chol depletion decreased both ER-PM contacts and chol surface exposure, consistent with the accumulation of ER-resident proteins at ER-PM contact sites upon chol supplementation [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 88%
“…MCS are specialized small areas of close apposition between two organelles and at the LE/Lys-ER interface, lipid and cholesterol transfer proteins, together with tethers, sorting nexins, membrane channels, SNAREs, small Rab-GTPases and annexins mediate ion and lipid exchange [9][10][11][12]145,146]. It would go beyond the scope of this review to list all MCS-associated proteins, and we recommend excellent reviews that address the association of MCS with cancer-related events for further reading [147][148][149][150]. Most important here, NPC1-dependent and -independent cholesterol transfer mechanisms across MCS between LE/Lys and the ER involve members of the StARD and ORP families, Rab7 and their regulators and effectors, as well as the scaffolding protein annexin AnxA6 [9][10][11][12]145,146], all of which with links to cancer that will be described in more detail in the following sections.…”
Section: Potential Roles Of Le/lys-chol Transfer Across Membrane Cont...mentioning
confidence: 99%
“…Indeed, mitochondria were found to be positioned at the cytosolic edge facing the ER, and in actual contact with ER Ca 2+ transporters [ 95 ]. The MCSs enable the exchange of signals involving a set of various proteins and contribute to mitochondrial Ca 2+ signalling due to the plausible uptake of ER-released Ca 2+ through the MCU, possibly via IP 3 R and MCU-associated proteins [ 98 , 99 ].…”
Section: Ca 2+ Transportome Composition and Functionmentioning
confidence: 99%